1993
DOI: 10.1128/aac.37.12.2557
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of dirithromycin with human polymorphonuclear leukocytes

Abstract: Dirithromycin, a new macrolide antibiotic, achieves prolonged, high levels in tissue. We previously demonstrated that certain macrolides are highly concentrated within phagocytic cells. This background information prompted us to evaluate the interactions of dirithromycin and human polymorphonuclear leukocytes (PMNs). After incubation with radiolabeled dirithromycin, antibiotic uptake by PMNs was determined by a velocity-gradient centrifugation technique and was expressed as the ratio of the cellular to the ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 25 publications
0
24
0
Order By: Relevance
“…By contrast, as we and others have already observed (16,39), dirithromycin uptake increased as a function of time; a similar but less striking phenomenon was observed with erythromycylamine.…”
Section: Methodsmentioning
confidence: 40%
“…By contrast, as we and others have already observed (16,39), dirithromycin uptake increased as a function of time; a similar but less striking phenomenon was observed with erythromycylamine.…”
Section: Methodsmentioning
confidence: 40%
“…In previous studies, we showed that certain antibiotics (clindamycin, several macrolides, and trimethoprim) are highly concentrated by human PMNs (16,19,21,32,37). Like pentoxifylline, these drugs inhibit the respiratory burst response in PMNs (16,17,29).…”
mentioning
confidence: 99%
“…Pentoxifylline inhibited the zymosan-stimulated increase in the uptake of adenosine but, surprisingly, actually augmented the phagocytosisinduced increase in clindamycin uptake by PMNs (14). Ingestion of microbial particles inhibits the accumulation of macrolide antibiotics (erythromycin, roxithromycin, and dirithromycin) by phagocytic cells (16,19,21,37).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Dirithromycin has been shown to have higher intracellular retention [26,29], probably because this molecule contains two basic sites for protonation, one on the desosamine sugar and the other at the C9 position of the lactone ring. Its long persistence in the cells may be attributable to this second amino group.…”
Section: Discussionmentioning
confidence: 99%